The Influence of Work Culture And Work Environment Work Environment on Employee Performance (Study on Medical Record Installation of Regional General Hospital Cibabat Cimahi City) - Septianawati, Dina; Komar Priatna, Deden; Avianti, Widiya (Greenation International Journal of Law and Social Sciences, 2023)
The aim of this research is to determine and analyze: (1) Work Culture (2) Work Environment; (3) Employee Performance; and (4) The influence of work culture and work environment on the performance of medical records installation employees at the Cibabat Regional General Hospital, Cimahi City, both simultaneously and partially.The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is the employees of the Medical Records Installation at the Cibabat Regional General Hospital, Cimahi City with a sample of 30 people. The type of investigation is causality, and the time horizon in this research is cross-sectional.Based on the research results, it was found that the work culture experienced by employees of the Medical Records Installation at the Cibabat Regional General Hospital, Cimahi City was good, the work environment at the Medical Records Installation at the Cibabat Regional General Hospital, Cimahi City could generally be said to be good, the performance of the employees at the Hospital Medical Records Installation In general, the Cibabat area of ??Cimahi City is currently considered good. Work Culture and Work Environment influence the Performance of Medical Records Installation Employees at the Cibabat Regional General Hospital, Cimahi City simultaneously and partially. However, partially the dominant work culture influences employee performance rather than the work environment.Because work culture predominantly influences performance, it is the first priority in improving performance. Therefore, the Medical Records Installation at the Cibabat Regional General Hospital, Cimahi City is recommended to improve working conditions and atmosphere, so that they are able to work more professionally